No-till improves selected soil properties, phosphorous availability and utilization efficiency, and soybean yield on some smallholder farms in South Africa - Chauke, Patience B.; Nciizah, Adornis D.; Wakindiki, Isaiah I. C.; Mudau, Fhatuwani N.; Madikiza, Seneo; Motsepe, Matiga; Kgakatsi, Ikalafeng (Frontiers in Sustainable Food Systems, 2022)
Some of the limiting factors for smallholder farmer soybean production in South Africa are low native soil phosphorus (P) availability and poor utilization efficiency of added P. Phosphorus fertilization, use of improved or high yield potential cultivars and appropriate cropping systems could increase soybean yields. The objective of this study was to determine the effects of tillage, cultivar and P fertilization levels on P uptake and P use efficiency, as well as plant growth, yield, grain protein and oil content, in a soybean based cropping system. The study was conducted under dryland conditions at Sheepmoor, Mpumalanga. A field experiment was established in a randomized complete block design. Treatments were arranged in a 2 × 3 × 3 strip-split-plot structure. There were two tillage systems [no-till (NT) and conventional tillage (CT)], three cultivars (PAN 1614R, PAN 1521R, and PAN 1532R), and three phosphorus rates (0, 30, and 60 kg/ha). All treatment combinations were replicated three times. P uptake improved with P application, although there were no differences between 30 and 60 kg/ha whilst PFP was significantly higher at 30 kg/ha P. Yield was significantly higher at 30 kg/ha P application under NT and varied with cultivars. P application at 30 and 60 kg/ha significantly reduced oil content by 11.3 and 7.16%, respectively, but had inverse effects on protein content. The activities of acid phosphatase (ACP) and alkaline phosphatase (ALP) also increased with P application. Improvement of soybean yield and its attributes, grain quality, P uptake, PFP, soil physicochemical and microbial properties emphasize the importance of fertilizer application, sustainable cropping systems coupled with careful cultivar selection. Therefore, in order to improve soil fertility and soybean yield under small farm conditions, the application of no-till and optimum application of fertilizers should be prioritized.